High-fat diet promotes lung fibrosis and attenuates airway eosinophilia after exposure to cockroach allergen in mice. (1st November 2013) - Ge, Xiao Na; Greenberg, Yana; Hosseinkhani, M. Reza; Long, Eric K.; Bahaie, Nooshin S.; Rao, Amrita; Ha, Sung Gil; Rao, Savita P.; Bernlohr, David A.; Sriramarao, P.
ABSTRACT: Obesity is an important risk factor for asthma but the mechanistic basis for this association is not well understood. In the current study, the impact of obesity on lung inflammatory responses after allergen exposure was investigated. C57BL/6 mice maintained on a high-fat diet (HFD) or a normal diet (ND) after weaning were sensitized and challenged with cockroach allergen (CRA). Airway inflammation was assessed based on inflammatory cell recruitment, measurement of lung Th1-Th2 cytokines, chemokines, eicosanoids, and other proinflammatory mediators as well as airway hyperresponsiveness (AHR). CRA-challenged mice fed a HFD exhibited significantly decreased allergen-induced airway eosinophilia along with reduced lung IL-5, IL-13, LTC4, CCL11, and CCL2 levels as well as reduced mucus secretion and smooth muscle mass compared to ND fed mice. However, allergen-challenged HFD fed mice demonstrated significantly increased PAI-1 and reduced PGE2 levels in the lung relative to corresponding ND fed mice. Interestingly, saline-exposed HFD fed mice demonstrated elevated baseline levels of TGF-β1, arginase-1, hypoxia-inducible factor-1α, and lung collagen expression associated with decreased lung function compared to corresponding ND fed mice. These studies indicate that a HFD inhibits airway eosinophilia while altering levels of PAI-1 and PGE2 in response to CRA in mice. Further, a HFD can lead to the development of lung fibrosis even in the absence of allergen exposure which could be due to innate elevated levels of specific profibrotic factors, potentially affecting lung function during asthma.